Determinación preliminar de fitoconstituyentes en rizomas de Niphidium albopunctatissimum Lellinger y su actividad frente al radical libre 2, 2-difenil-1- picrilhidrazilo - Cabanillas Vargas, Yesica Yanet (2018)
The main objective of this research work was to determine the phytoconstituents present in rhizomes of Niphidium albopunctatissimum Lellinger and their activity against the free radical 2, 2-diphenyl-1-picrylhydrazyl. The fluid extract of the rhizomes of Niphidium albopunctatissimum Lellinger (calaguala) from the Queropuspo sector, Ahijadero farm, Cospán district, Cajamarca province, Cajamarca department (Peru) was used. For the phytochemical determination the method of Dr. Olga Lock "Test to the drop" was followed. The identified phytoconstituents were polyphenols, anthocyanidins, saponins, tannins and reducing sugars. The activity against the 2, 2-diphenyl-1-picrylhydrazyl free radical was determined using the method described by Brand Williams modified, where it was faced with the fluid extract of the rhizomes of Niphidium albopunctatissimum Lellinger with a solution of DPPH· at a concentration of 0.1mM (0.04 mg / mL); and read at a wavelength of 516 nm. It is concluded that the rhizomes of Niphidium albopunctatissimum L. have an antioxidant capacity with a capture percentage of free radical 2, 2-diphenyl-1-picrylhydrazil of 55.5% and an IC50 of 1.705 μg / mL, so they could be used as natural antioxidants, due to the presence of polyphenols, anthocyanidins, saponins and tannins in the fluid extract of the calaguala